Inflation and the Stock Market: Reply - Feldstein, Martin (American Economic Review, 1982)
The very poor performance of the stock market has been one of the major economic puzzles of the 1970's. The value of common stock has fallen significantly in relation to the price of final goods, the replacement value of the capital stock, and the value of pretax equity earnings. This fall in real share prices has raised the cost of capital to firms and has thereby reduced the incentive to invest in plant and equipment. Although no single factor is likely to have been responsible for this unusual performance of share prices, I believe that the sharp rise in during the past fifteen years has been one of the significant causes. Of course, should have no effect on real share values in an economy in which there are no taxes or other imperfections and in which portfolio investors correctly distinguish real and nominal magnitudes.' But the U.S. economy does have substantial taxes that are assessed on the basis of nominal (rather than real) capital income.2 An increase in the rate of raises the effective tax rate on equity earnings relative to the tax rate on other types of investment income. Individuals and financial institutions will therefore hold the existing stock of equity capital only at a lower real price. In Inflation and the Stock Market I presented a very simple model designed to capture the essential feature of this tax nonneutrality and its impact on share prices. The primary purpose of the analysis was to show how the overstatement of taxable profits caused by (because of historic cost depreciation and inventory accounting rules) could lead to lower real share prices even though reduced the real net-of-tax return on debt. This explanation stands in sharp contrast to the conventional view that lowers share prices because the (nominal) yield on debt rises. A second purpose of the analysis was to show how corporate stock could be a good hedge against inflation as long as the rate remained constant while being adversely affected by increases in the expected rate of inflation. And, finally, I wanted to indicate the importance of recognizing separately the roles of tax-exempt institutional investors and taxable individual investors. The analysis was definitely not intended to prove that must cause share prices to decline with existing U.S. tax rules. The model that I used is clearly far too simple in several ways to do more than illustrate a possible line of influence. The model assumes, among other things, that there are no retained earnings, no corporate debt finance, and no individual investment opportunities other than corporate stocks and government bonds.3 But the simplified model has the virtue of tractability and clarity that would be lost by adopting a more complex specification. In their comment, Irwin Friend and Joel Hasbrouck have presented a slightly different model of asset demand in an economy with taxes and inflation. I think that this alternative model is a useful complement to my own analysis. Moreover, as I shall explain in this reply, their model has the same implications as mine about the effect of on share prices. *President, National Bureau of Economic Research, and professor of economics, Harvard University. The study discussed in this note is part of the NBER Study of Capital Formation. The views expressed here are my own and not those of the NBER. 'Franco Modigliani and Richard Cohn have argued that many investors do not correctly evaluate either real profits or the relevant discount rate because they do not distinguish between real and nominal interest rates. 2This includes the use of historic cost depreciation, artificial inventory profits based on FIFO accounting, nominal interest income and expenses, and nominal capital gains. 3These features are included in a later model (see my 1980b article) designed to explain more of the complexities of the tax-inflation interaction.